Nutrientes e metais pesados em um latossolo vermelho em função de doses de lodo de esgoto - Maas, Greyce Charllyne Benedet (2011)
The objective of this study was to evaluate the influence of increasing sewage sludge levels on the concentration of nutrients and heavy metals in an Oxisol. The experiment was established in a greenhouse using columns of lixiviation, by means of a completely randomized experimental design with four repetitions. In the column, the treatments were four sludge dosages, in the percolated water the treatments were distributed in a split-plot design with four sludge dosages and four time series representing rainfall (simulated). The sludge dosages were as follows: 0 (control); 2.5; 5.0and 7.5 t ha-1 (dry weight). The characteristics evaluated in the column were pH, Ca+2 e Mg+2, Al+3, H + Al, K+ , Na+ , P, CEC, Cu, Fe, Mn, Zn, Cd, Ni, Cr e Pb, total nitrogen (TN), total organic carbon (TOC) and electrical conductivity. The characteristics evaluated in percolated water were pH, electrical conductivity, sodium, potassium, phosphate and nitrate. Increased sludge level diminished pH, increased electric conductivity, organic matter as well as manganese and cupper available in the soil. Manganese was the only element to increase in all soil layers analyzed. No change in potassium, phosphorus, total nitrogen, iron, and zinc were noticed. Nitrate content increased with increasing sludge level and simulated rain fall. Nutrient concentrations were within the limits established by the current legislation, but nitrate in percolated water was beyond such limits. Heavy metals did not represent risk of soil contamination due to the low concentration of sludge used in the study.